The effects of coach-athlete working alliance on affect, worry and performance satisfaction among junior elite athletes - Moen, F.; Hrozanova, M.; Myhre, K. (International Journal of Applied Sports Sciences, 2017)
The current study aimed to explore the association between subjective performance and coach-athlete working alliance, positive and negative affect, and worry among Norwegian junior elite athletes. A sample of 358 junior elite athletes from 3 different high schools specialized in sports participated in the investigation. A theoretical model was tested, in which working alliance between coaches and athletes was expected to be associated with positive and negative affect, worry and subjective performance. Results show that this theoretical model explains 27% of the variance in subjective performance, whereas working alliance is significantly associated with positive and negative affect. Furthermore, worry, and positive and negative affect are significantly associated with subjective performance, while worry is significantly associated with negative affect. These results are discussed based on the Cognitive Activation Theory of Stress, and indicate that there are three crucial facets essential for building an effective coach-athlete relationship. These include, firstly, coaches` abilities to establish strong emotional bonds with their athletes; secondly, coaches` competence in setting goals that are mutually understood; and thirdly, determination of tasks which are perceived by athletes as helpful in goal attainment.